Federalismo e descentralização do SUS : formação de um regime polarizado de relações intergovernamentais na década de 1990 - Ouverney, Assis Luiz Mafort (2015)
This thesis aimed to explain the political and institutional dynamics that polarized the intergovernmental relations in health policy at the end of the 1990s. Polarization was characterized by the simultaneous presence of a significant degree of decentralization and high normative and financial regulatory capacity of the Ministry of Health. In the Brazilian literature, previous approaches produced partial explanations based on specific variables. These includes the option for a highly decentralized health system of the Constitution of 1988, the preferences of the Sanitary Reform Movement for local policies, Basic Operational Norms – NOBs content, historical legacy of centralized health policies and the agenda of economic reforms in the 90’s, among others. This thesis proposes a Historical-Institutionalist explanation that integrates all this conditioning factors around a sequential explanation of health sector reform. In this approach, the trajectory of intergovernmental relations is the result of a long chain of decisions taken in concrete political contexts of the three governments in the 90s (Collor, Itamar and FHC). The choices of a government affected the range of options available to the next one, producing a dynamics of path dependence. Therefore, polarization is an unintended outcome of a sequence of decisions that concentrated power, responsibilities and resources simultaneously in the Ministry of Health and municipalities.